Animal-inspired fashion terms (based on Vogue and Harper’s Bazaar, 2020–2025) - Романова, Вероніка Олександрівна (Київський національний університет імені Тараса Шевченка, 2025)
This bachelor’s thesis investigates animal-inspired terminology in the sphere of fashion in the English language. The relevance of the study arises from a growing interdisciplinary interest in the interplay between language, fashion, and culture, as fashion operates not only as an industry but also as a semiotic system in which meaning is constructed through both verbal and visual codes. The object of the study is contemporary English fashion terminology, while the subject encompasses the thematic and structural features of animal-inspired terms, as well as their linguistic and stylistic functions. The aim of the research is to analyse the lexical, structural, and functional characteristics of fashion terminology inspired by animal imagery. To this end, the study employs methods of total sampling, componential analysis, morphological and syntactic analysis, stylistic analysis, classification, and descriptive techniques. The analysis reveals that, structurally, animal-inspired fashion terms are represented by simple lexemes, derivatives, and complex compounds of various types, including endocentric, exocentric, copulative, appositional, and hybrid constructions. Thematically, these terms can be grouped into semantic categories such as visual representation, material origin, anatomical references, metaphorical associations, and branding. The study identifies that these terms perform nominative, expressive, evaluative, marketing, cognitive, and cultural-semiotic functions. Metaphorical extensions, in particular, are shown to enrich fashion discourse with emotional resonance, vivid imagery, and cultural depth. The results of the analysis show that animal-inspired terms constitute a diverse and multidimensional component of fashion discourse, reflecting current socio-cultural trends. They perform not only an informative function, but also act as instruments for shaping image -based senses that can influence the perception of fashion and consumer behavior.

Бакалаврську роботу присвячено дослідженню анімалістичної термінології моди в англійській мові. Актуальність теми зумовлена зростанням міждисциплінарного інтересу до взаємодії мови, моди та культури, адже мода функціонує не лише як індустрія, а й як семіотична система, у якій значення формуються через вербальні та візуальні коди. Об’єктом дослідження є англійська термінологія моди сучасного періоду, а предметом – тематичні й структурні особливості термінологічних одиниць, що містять назви тварин, а також їхні лінгвістичні та стилістичні функції. Метою роботи є аналіз лексичних, структурних та функціональних характеристик термінів моди, у складі яких наявні номінації тварин. Для досягнення цієї мети використано методи суцільної вибірки, компонентного, морфологічного, синтаксичного та стилістичного аналізу, а також метод класифікації та описовий метод. У результаті дослідження встановлено, що з погляду структури відповідні терміни представлені простими лексемами, похідними одиницями та складними композитами, зокрема ендоцентричними, екзоцентричними, апозитивними, гібридними конструкціями тощо. Тематично їх можна класифікувати у такі групи: візуальна репрезентація, матеріал походження, анатомічні референції, метафоричні асоціації та назви брендів. Виявлено, що ці терміни виконують номінативну, експресивну, оцінну, маркетингову, когнітивну та культурно-семіотичну функції. Особливу цінність мають метафоричні розширення, що надають дискурсу моди емоційності, образності та культурної значущості. Результати аналізу засвідчують, що терміни з анімалістичним компонентом становлять багатовимірну складову дискурсу моди, відображаючи сучасні соціокультурні тенденції. Вони виконують не лише інформативну функцію, а й виступають інструментами формування іміджевих смислів, здатних впливати на сприйняття моди та поведінку споживачів.
Keywords: fashion terminology; animal-inspired term; structural classification; thematic classification; термінологія моди; анімалістичний термін; структурна класифікація; тематична класифікація